THE EFFECT OF DISCIPLINE AND COMPENSATION ON EMPLOYEE PERFORMANCE AT PT BUMI REKSA NUSA SEJATI THROUGH MOTIVATION AS VARIABLE INTERVENING - Saparudin Saparudin; Suhardi Suhardi (Jurnal Ekonomi, 2023)
The purpose of this study is to determine partially and simultaneously Discipline and Compensation on Employee Performance through Motivation as an Intervening variable. The population in this study was 160 employees of PT Bumi Reksa Nusa Sejati. The sampling technique used the calculation of the Slovin formula with a total of 115 respondents. The data collection uses a Likert scale questionnaire. Data analysis using multiple linear regression analysis. Data processing using SPSS 22 software. The value of Equation 1 of the discipline variable, the t-count value is 4.735 > t-table 1.658, and the t-count value of the compensation variable is 11.920 > t-table 1.658. This shows that the independent variables together have an effect on the motivational variable with a determination coefficient of 0.792 (79.2%) and the remaining 20.8% is influenced by other factors which are not present in this study. For the equation value of the 2 discipline variables, the t-count value is 6.202 > t-table 1.658, the t-count value for the compensation variable is 2.060 > t-table 1.658, the t-count value for the motivational variable is 2.977 > 1.658. The indirect effect value of the discipline variable through motivation is 0.52 <0.435 direct effects, and the indirect effect value of compensation through motivation is 0.412 > 0.198 direct effect. This shows that the independent variables together have an influence on the dependent variable with a coefficient of determination of 0.745 (74.5 %) and the remaining 25.5% is influenced by other factors that are not present in this study